Three-dimensional numerical simulation of solidification microporosity and microstructure of aluminum alloys. Issue 1 (May 2020) - Gu, C; Luo, A A
Abstract: A three-dimensional model was developed to study microporosity evolution with grain growth during solidification by cellular automaton method. The simulations are able to show the evolution and morphology of both grain structure and porosity. The effects of shrinkage pressure and initial hydrogen content on porosity evolution and final porosity percentage are modeled and related to the location-specific microstructure of the solidified products. A wedge die casting, providing samples of different cooling rates, was used to validate the simulation results. X-ray micro-tomography was performed to obtain the relevant porosity information. The simulated porosity size, percentage and distribution considering both shrinkage pressure and hydrogen content were found to agree well with those from experimental measurements.